Field Evidence of Colonisation by Holm Oak, at the Northern Margin of Its Distribution Range, during the Anthropocene Period - Delzon, Sylvain; Urli, Morgane; Samalens, Jean-Charles; Lamy, Jean-Baptiste; Lischke, Heike; Sin, Fabrice; Zimmermann, Niklaus E.; Porte, Annabel J. (PLOS ONE, 2013)
A major unknown in the context of current climate change is the extent to which populations of slowly migrating species, such as trees, will track shifting climates. Niche modelling generally predicts substantial northward shifts of suitable habitats. There is therefore an urgent need for field-based forest observations to corroborate these extensive model simulations. We used forest inventory data providing presence/absence information from just over a century (1880-2010) for a Mediterranean species (Quercus ilex) in forests located at the northern edge of its distribution. The main goals of the study were (i) to investigate whether this species has actually spread into new areas during the Anthropocene period and (ii) to provide a direct estimation of tree migration rate. We show that Q. ilex has colonised substantial new areas over the last century. However, the maximum rate of colonisation by this species (22 to 57 m/year) was much slower than predicted by the models and necessary to follow changes in habitat suitability since 1880. Our results suggest that the rates of tree dispersion and establishment may also be too low to track shifts in bioclimatic envelopes in the future. The inclusion of contemporary, rather than historical, migration rates into models should improve our understanding of the response of species to climate change.
APSAPSThe following values have no corresponding Zotero field: pub-location: 1160 BATTERY STREET, STE 100, SAN FRANCISCO, CA 94111 USA publisher: PUBLIC LIBRARY SCIENCE
Keywords: mediterranean species; niche modelling; Quercus ilex

Growth and maintenance costs of leaves and roots in two populations of Quercus ilex native to distinct substrates - Laureano, Raquel G.; García-Nogales, Ana; Seco, José I.; Rodríguez, Jesús G. P.; Linares, Juan C.; Martínez, Feliciano; Merino, José (Plant and Soil, 2012)
Aims This work tests the hypothesis that growth and maintenance costs of plant organs are higher in more stressful soils. Methods Two populations of Quercus ilex L were selected in the southern Iberian Peninsula, these growing in similar climates but different soil types, namely a brown well-developed soil on slate rock, and a stressful lithosol on gypsum rock. In both localities, growth and maintenance respiration were measured in undetached young and mature leaves (trees under natural conditions) and fine roots (hydroponically grown seedling). Results Young leaves of the two populations displayed an almost identical growth cost (1.53 g glucose g -1 ). The maintenance cost was higher in the young (40.2 vs. 25.3 mg glucose g -1 day -1 ; P<0.05) and in the mature (7.64 vs. 4.33 mg glucose g -1 day -1 ; P<0.001) leaves of individuals growing in gypsum soils. The growth cost of fine roots was the same in both populations (1.18 g glucose g -1 ) while the maintenance cost was higher in the Gypsum population (8.95 vs. 7.39 mg glucose g -1 day -1 ; P<0.01). Conclusions The results show for first time that the cost of organ maintenance may be related to the degree of soil stress in their native habitats.
Keywords: ecotypes; evergreen leaves; growth respiration; maintenance respiration; mediterranean species; root respiration; sclerophylly; soil stress

Photoprotective responses of Mediterranean and Atlantic trees to the extreme heat-wave of summer 2003 in Southwestern Europe - García-Plazaola, José Ignacio; Esteban, Raquel; Hormaetxe, Koldobika; Fernández-Marín, Beatriz; Becerril, José Maria (Trees, 2008)
Summer 2003 was extremely hot in Europe. High light in combination with heat and drought exacerbates the generation of photo-oxidative stress. Under these conditions photoprotective responses can be critical for plant survival. Photoprotection was analysed in 2003 in several Mediterranean and Atlantic woody species. These data were compared with previous summers (1998, 1999 and 2001) to evaluate the potential acclimation for each species. A pattern of changes consisting on a decrease in chlorophyll, ascorbate and Fv/Fm and an increase in tocopherol, xanthophyll cycle pigments (VAZ) and deepoxidation index was regularly observed. Acclimation potential was measured by the use of the plasticity index for each parameter. Mediterranean species were more plastic than Atlantic ones. The latter were unable to increase antioxidant pools to the same extent or to downregulate the efﬁciency of light energy conversion. These results indicate that most Mediterranean species are able to perform an efﬁcient acclimation to heat stress, whilst Atlantic species will be more affected by climate warming.
Keywords: á summer 2003; antioxidants; antioxidants á heat-wave á; heat-wave; mediterranean species; mediterranean species á photoprotection; photoprotection; summer 2003

Comparative water relations of four Mediterranean oak species - Acherar, M.; Rambal, S. (Plant Ecology, 1992)
The water relations and responses of two evergreen (Quercus ilex L. and Q. suber L.) and two decidu- ous (S. afares Pomel. and Q. faginea Will.) Quercus species were studied under experimental conditions. Two-year old seedlings grown in 30 1. pots were subjected to a drying period during which stomatal conductance, pre-dawn potential and minimum foliar potential were measured. The results shows that, for all species, the daily course of stomatal conductance agrees with the patterns proposed by Hinckley et al. (1978 & 1983). Concurrent with the species responses to short-term variation in water availability, it was found that pre-dawn leaf water potential controlled the maximum daily leaf conductance. There was a strong correlation between pre-dawn leaf potential and maximum daily conductance as described by the reciprocal function g ........ = ( -0.47 + 2.61.~bp) 1 for the evergreen oaks and g ......... (-1.94+7.39.~bp) 1 for the deciduous species. These differences between the two groups may partialy explain their geograhic distributions, and suggest general questions concerning the mechanisms which optimize water-use efficiency in Mediterranean oak species.
Keywords: mediterranean species; Quercus; Stomatal conductance; water-potential; water-stress